Otimização dos parâmetros estruturais da plataforma Stewart para uma tarefa determinada - Santos, Fábio Pacholok dos (2015)
This work aims at reporting a methodology of optimal design of a parallel manipulator with six degrees of freedom. Several research papers related to the topic of this work were studied in order to establish the kinematic modeling of manipulator. Then, the simulation of the kinetics modeling was implemented in the software MATLAB. The optimization to maximize the kinematic dexterity of the manipulator was solved by using Genetic Algorithm. The structural parameters of the Stewart-Goug platform were obtained and these results were analyzed. The introduced in this work demonstrated to be effective to determine the structure parameters to improve the kinematic performance of the parallel mechanism.